Enzymatic catalysis of hydrocarbons oxidation “in vitro” (review) - Zeynalov, Eldar; Nagiev, Tofik (Publishing House of Lviv Polytechnic National University, 2015)
Reactions proceeding at ambient temperature very promptly and selectively, as it occurs in live organisms, imitation of the wildlife processes, and, eventually, study of mechanism of enzymes action are important challenges of contemporary chemistry. This short review gives information on recent achievements in the field of enzymatic catalysis of oxidation of hydrocarbons. The literature material was gathered using the Thomson Reuters electronic database (Web of Science) and mostly covers the last decades. Розглянуто важливі проблеми сучасної хімії – швидкий і селективний перебіг реакції за звичайних умов, як це відбувається в живих організмах, імітація процесів з життя живої природи, вивчення механізму дії ферментів. Представлено інформацію про останні досягнення в області ферментативного каталізу окиснення вуглеводнів. Приведено огляд джерел літератури за останні десятиліття з використанням електронної бази Thomson Reuters (Web of Science).
Ферментативний каталіз окиснення вуглеводнів «in vitro» (огляд)
Keywords: enzyme; oxidereductase; hydrocarbon; aerobic oxidation; biocatalysis; organic pollutant; biodegradation; ензим; оксиредуктаза; вуглеводень; аеробне окиснення; біокаталіз; органічний забруднювач; біодеструкція